Association between fasting blood glucose and psychotic symptoms in Chinese patients with first-episode drug-naïve major depressive disorder - Xingzhi Xia; Hanxu Deng; Wei Ren; Lin Yang; Yingzhao Zhu; Yaozhi Liu; Junjun Liu; Xueli Zhao; Fengnan Jia; Xiangdong Du; Xiangyang Zhang (BMC Psychiatry)
Abstract Introduction Psychotic depression (PD) is a highly debilitating disorder characterized by hallucinations and/or delusions accompanied by depression. A variety of neurotransmitters, hormones and corresponding receptors in the endocrine system are involved in the onset and progression of depression, and fasting blood glucose (FBG) can be an important indicator for monitoring the stability of the endocrine system. The aim of this study was to investigate the relationship between FBG and PD in a Chinese population with first-episode drug-naïve (FEDN) major depressive disorder (MDD). Methods In this study, 1718 outpatient individuals diagnosed with first-episode drug-naïve major depressive disorder (FEDN MDD) were included. The association between PD and FBG levels was identified through multivariable binary logistic regression analysis. To investigate potential non-linear relationships, a two-piecewise linear regression model was utilized. Additionally, interaction and stratified analyses were performed based on gender, educational background, marital status, presence of comorbid anxiety, and history of suicide attempt. Results Multivariate logistic regression analysis showed that FBG was positively associated with the risk of PD in FEDN MDD patients (OR = 1.68, 95% CI: 1.31 to 2.13; P < 0.05). Smoothed plots showed a non-linear relationship between FBG and PD, while the inflection point of FBG was calculated using a two-segmented logistic regression model to be 6.23 mmol/L. On the right side of the inflection point, the probability of PD increased substantially by 278% (OR = 3.78, 95% CI: 1.75 to 8.18, p < 0.001), while no significant association was observed on the left side of the inflection point (OR = 1.06, 95% CI: 0.73 to 1.52, p = 0.772). Conclusions Our investigation revealed a nonlinear relationship between FBG and PD in patients with FEDN MDD, thereby informing more effective intervention strategies for managing psychotic symptoms in individuals with depression.